Multiphysical Field Modulated VO2 Device for Information Encryption - Shanguang Zhao; Liang Li; Changlong Hu; Bowen Li; Meiling Liu; Jinglin Zhu; Ting Zhou; Weidong Shi; Chongwen Zou (Advanced Science, 2023)
Abstract In the information explosion society, information security is highly demanded in the practical application, which raised a surge of interest in designing secure and reliable information transmission channels based on the inherent properties of emerging devices. Here, an innovative strategy to achieve the data encryption and reading during the data confidential transmission based on VO2 device is proposed. Owing to the specific insulator‐to‐metal transition property of VO2, the phase transitions between the insulator and metallic states are modulated by the combination of electric field, temperature, and light radiation. These external stimulus‐induced phase diagram is directly associated with the defined VO2 device, which are applicable for control the “0” or “1” electrical logic state for the information encryption. A prototype device is fabricated on an epitaxial VO2 film, which displayed a unique data encryption function with excellent stability. The current study not only demonstrated a multiphysical field‐modulated VO2 device for information encryption, but also supplied some clues for functional devices applications in other correlated oxide materials.